Pengaruh Bagi Hasil, Disposable income, dan Promosi Terhadap Minat Menabung Mahasiswa di Bank Syari’ah - Fanny Putri Ayu Hariati; Rochmawati Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
This research was carried out with the aim of knowing the influence on Profit Sharing, Disposable income, and Promotion with Saving Interests in Students of the Accounting Education Department at Islamic Banks. This study uses quantitative research methods and the data in this study were collected through questionnaires. A total of 61 students in the 2018 Accounting Education Study Program, State University of Surabaya were used as the population and sample in this study. Saturated Sampling technique was used in this study. One of the non-parametric analytical tests of Kendall's Tau-b was used to analyze this research through the SPSS version 25 computer program. According to the analytical test that has been carried out, it can be stated that: (1) Profit Sharing has a significant effect on the Interest in Savings variable with a value of 0.048. (2) Disposable Income has a significant effect on Saving Interest with a value of 0.000. (3) Promotion has a significant effect on Saving Interest with a value of 0.000. So it can be conluded that the variable of Profit Sharing, Disposable Income, and Promotion affect the Student Saving Interest variable.